Centring the periphery: northern Morocco as a hub of transnational anti-colonial activism, 1930–43*. Issue 3 (11th October 2016) - Stenner, David
Abstract: During the interwar years, Moroccan anti-colonial activists organized a propaganda campaign abroad to discredit the French and Spanish protectorates that had been established in 1912. Yet it was not the famous nationalist leaders from the country's major urban centres but a small group from the marginalized northern city of Tetuan that played a pivotal role in the internationalization of the Moroccan question. This article demonstrates that, by analysing the emergence of Morocco's nationalist movement through a transnational framework, rather than within the confines of the nation-state, we can rearrange the geographical and political hierarchies of local history as previously disregarded individuals and locations suddenly emerge to the forefront of the narrative.